(untitled) (Bangladesh Journal of Livestock Research, 2021)
The in vitro embryo production (IVP) technology has emerged as a potential biotechnological approach to multiply genetically high yielding dairy cows. Its commercial application is increasing in many developed and developing countries over the years. Bangladesh livestock Research Institute (BLRI) adopted in vitro embryo production protocol from bovine ovaries of slaughterhouse. However, the risks of transmission of contagious diseases like Brucella abortus with embryos are not evaluated so far. Considering these facts, the present experiments were conducted to evaluate the efficiency of in vitro embryo production protocol with slaughterhouse ovaries as well as risk of contamination of produced embryos with Brucella abortus. To identify sources of contamination of embryos with Brucella abortus (if any), the laboratory water, different media used in the IVP process, semen, and follicular fluids were evaluated for confirmation of the organisms. In addition, vaginal swabs were collected from 2 buffaloes aborted due to suspected Brucella abortus infection. Molecular test were used to detect Brucella abortus contamination. Brucella abortus specific PCR product was not detected on agarose gel electrophoresis. The efficiency of IVP measured by cleavage and blastocyst development rates were 75.5±2.7% and 16.6±3.9%, respectively. The present study inferred that the in vitro produce embryos are free from Brucella abortus infection. Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 105-112